2008
DOI: 10.1007/s11837-008-0068-1
|View full text |Cite
|
Sign up to set email alerts
|

Aging and fracture of human cortical bone and tooth dentin

Abstract: Mineralized tissues, such as bone and tooth dentin, serve as structural materials in the human body and, as such, have evolved to resist fracture. In assessing their quantitative fracture resistance or toughness, it is important to distinguish between intrinsic toughening mechanisms which function ahead of the crack tip, such as plasticity in metals, and extrinsic mechanisms which function primarily behind the tip, such as crack bridging in ceramics. Bone and dentin derive their resistance to fracture principa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
0
5
1
Order By: Relevance
“…There are also some changes in the mineralized collagen matrix with aging, but this is less well understood [98, 99]. Independent studies of the R-curve behavior for crack extension parallel (in plane) [100, 101] and perpendicular [102] to the dentin tubules report significant reductions in the crack growth resistance of dentin with age. Yet, studies of the fatigue behavior have reported slightly conflicting responses.…”
Section: Fatigue Behaviormentioning
confidence: 99%
“…There are also some changes in the mineralized collagen matrix with aging, but this is less well understood [98, 99]. Independent studies of the R-curve behavior for crack extension parallel (in plane) [100, 101] and perpendicular [102] to the dentin tubules report significant reductions in the crack growth resistance of dentin with age. Yet, studies of the fatigue behavior have reported slightly conflicting responses.…”
Section: Fatigue Behaviormentioning
confidence: 99%
“…As expected, detrimental changes in the fracture toughness of dentin occur with increasing patient age. Independent studies of crack extension parallel and perpendicular to the dentin tubules show that “old” dentin undergoes a reduction in the crack growth resistance in both orientations. However, there are some unique qualities of the responses.…”
Section: Aging Of Dentinmentioning
confidence: 99%
“…Recent effort has been devoted to the experimental characterization and modeling of the dependence of the fracture resistance of biological composites on the crack length, the so-call "crack extension resistance curve" (R-curve) behavior (Nalla et al, 2003(Nalla et al, , 2004(Nalla et al, , 2005Kinney and Ritchie, 2005;Koester et al, 2008;Launey and Ritchie, 2009;Launey et al, 2010). To the best of our knowledge, much less attention has been given to the increase in fracture resistance due to the finite velocity of cracks, in spite of the fact that even small velocities may generate a non-negligible contribution to the fracture resistance (Sasaki et al, 1993;Okumura, 2002aOkumura, , 2003Ji and Gao, 2004;Iyo et al, 2004).…”
Section: Introductionmentioning
confidence: 99%